Wewnątrzrodzinne zróżnicowanie wzorów listewek skórnych w strefie podpalcowej stóp - Buchwald, Wiesław (Polskie Towarzystwo Antropologiczne, 1994)
INTRAFAMILIAL VARIABILITY OF DERMAL RIDGE PATTERNS IN SUBDIGITAL AREAS OF FEET was investigated on a sample of 700 families from northern Poland. Interdependence was measured (x2, cp), and frequencies of homo- and heterolateral similarities were calculated. Moreover, differences between parents and children in patterns of particular subdigital areas were investigated.
INTRAFAMILIAL VARIABILITY OF DERMAL RIDGE PATTERNS IN SUBDIGITAL AREAS OF FEET